2017
DOI: 10.1002/ece3.3292
|View full text |Cite
|
Sign up to set email alerts
|

Herbivore and pathogen effects on tree growth are additive, but mediated by tree diversity and plant traits

Abstract: Herbivores and fungal pathogens are key drivers of plant community composition and functioning. The effects of herbivores and pathogens are mediated by the diversity and functional characteristics of their host plants. However, the combined effects of herbivory and pathogen damage, and their consequences for plant performance, have not yet been addressed in the context of biodiversity–ecosystem functioning research. We analyzed the relationships between herbivory, fungal pathogen damage and their effects on tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 75 publications
2
33
2
Order By: Relevance
“…We are aware that we could not account for physiological responses, diversity‐mediated effects of herbivory and pathogens, or belowground interactions which have been shown to be additional important factors for tree growth (Ishii & Asano ; Bu et al ; Schuldt et al ). Variation in topography and soil conditions may also effect tree growth but those factors were found to be of weak explanatory power in the BEF‐China experiment (Kröber et al ; Fichtner et al ).…”
Section: Discussionmentioning
confidence: 99%
“…We are aware that we could not account for physiological responses, diversity‐mediated effects of herbivory and pathogens, or belowground interactions which have been shown to be additional important factors for tree growth (Ishii & Asano ; Bu et al ; Schuldt et al ). Variation in topography and soil conditions may also effect tree growth but those factors were found to be of weak explanatory power in the BEF‐China experiment (Kröber et al ; Fichtner et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Infection of a host tree by fungal pathogens is thus an important but often neglected factor that can drive associational resistance. For instance, Schuldt et al (2017) reported a positive relationship between damage of foliar herbivores and pathogens, which resulted in additive negative effects on tree growth. However tree species richness lead to AS to insects but AR to pathogens, with an overall reduced impact of both damaging agents combined on tree growth.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, tree diversity effects on pathogens have been less frequently investigated than for insect pests (Hantsch et al, 2014;Jactel & Brockerhoff, 2007;Pearse & Hipp, 2009). Even fewer studies have considered diversity effects on both pests and pathogens together, despite the potential for multitrophic interactions which could impact upon associational effects (Schuldt et al, 2017). For instance, initial damage to a plant by insect herbivores or pathogens can have both a reciprocal and antagonistic effect on subsequent plant attackers, via cross-talk between plant defense signaling pathways that are induced following attack (Moreira, Abdala-Roberts, & Castagneyrol, 2018).…”
mentioning
confidence: 99%